Immigration Wage Effects by Origin1. (20th February 2014) - Bratsberg, Bernt; Raaum, Oddbjørn; Røed, Marianne; Schøne, Pål
Abstract We estimate the direct partial wage effects of immigrant‐induced increases in labor supply, using the national skill cell approach with longitudinal records drawn from Norwegian administrative registers. The results show overall negative but heterogeneous wage effects, with larger effects on immigrant wages than on native wages and with native wages more responsive to inflows from Nordic countries than from developing countries. These patterns are consistent with natives and Nordic citizens being close substitutes, while natives and immigrants from developing countries are imperfect substitutes. Estimates are sensitive to accounting for effective immigrant experience, selective native participation, and variation in demand conditions and native labor supply.